On Context-Orientation in Aggregate Programming - Casadei, Roberto; Pianini, Danilo; Salvaneschi, Guido; Viroli, Mirko (2019 IEEE 4th International Workshops on Foundations and Applications of Self Systems (FASW), 2019)
Context-awareness plays a central role in self-adaptive software. By a programming perspective, context is often used implicitly, and context-aware code is fragmented in the codebase. In Context-Oriented Programming, instead, context is considered a first-class citizen and is explicitly used to modularise context-sensitive functionality and behavioural variability. In this paper, we reflect on the role of context in collective adaptive systems, by a discussion from the special perspective of a macro paradigm, Aggregate Programming, which supports the specification of collective behaviour by a global perspective through functional compositions of field computations. In particular, we consider the abstractions exposed in Context-Oriented and Aggregate Programming, suggest potential synergies in both directions, and accordingly take the first steps towards a combined design.